In situ single‐step reduction and silicidation of MoO3 to form MoSi2. Issue 3 (3rd September 2018) - Sharma, Piyush; Kaur, Taranpreet; Pandey, Om Prakash
Abstract: Nanocrystalline molybdenum disilicide (MoSi2 ) is synthesized in a specially designed autoclave at 900°C. The XRD results revealed that the formation of MoSi2 is favorable with the blend of MoO3, Si, and Mg powders. The HR‐TEM and SAED patterns confirm the formation of MoSi2 phase. The structural parameters (crystallite size, strain, stress, and deformation energy density) are calculated using the Williamson‐Hall (W‐H) analysis. The formation mechanism involved in the synthesis of MoSi2 is proposed. The nonisothermal oxidation kinetics ( 1200°C) of MoSi2 phase is examined through the thermal analysis techniques. The activation energy is determined by the Kissinger‐Akahira‐Sunsose isoconversional kinetic model. Finally, the reaction mechanism involved during the oxidation of MoSi2 phase is identified using the integral master‐plots method. Abstract : Formation mechanism and non‐isothermal oxidation kinetics of molybdenum disilicide (MoSi2 ).